ОЗЕРА НИЖНЕГО АМУРА. СТАТЬЯ 2. ГЕОМОРФОЛОГИЯ И МОРФОТЕКТОНИКА ОЗЕРНЫХ КОТЛОВИН - Уфимцев Г.Ф.; Щетников А.А.; Алексеенко С.Н. (My University, 2005)
The geomorphology of the lake shorelands and surrounding areas is described. The factors of lake morphogene-sis, the main of which is neotectonics, are discussed. Special attention is paid to social importance of the lake stock of the region.
Keywords: 551.435.38>556.557(-925.17)